2015
DOI: 10.1182/blood-2015-01-553974
|View full text |Cite
|
Sign up to set email alerts
|

How I treat Waldenström macroglobulinemia

Abstract: Waldenström macroglobulinemia (WM) is a B-cell neoplasm manifested by the accumulation of clonal immunoglobulin (Ig)M-secreting lymphoplasmacytic cells. MYD88 and CXCR4 warts, hypogammaglobulinemia, infections, myelokathexis syndrome-like somatic mutations are present in >90% and 30% to 35% of WM patients, respectively, and impact disease presentation, treatment outcome, and overall survival. Familial predisposition is common in WM. Asymptomatic patients should be observed. Patients with disease-related hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
140
1
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 176 publications
(153 citation statements)
references
References 109 publications
6
140
1
6
Order By: Relevance
“…All patients underwent FDG PET/CT before and after therapy. This imaging procedure was able to detect positive findings in 83 % of the patients, a result in sharp contrast with the data of previous studies carried out with the use of conventional imaging that reported liver, spleen, and lymph node involvement in remarkably lower percentages [79]. At baseline, FDG-avid sites included more frequently lymph nodes, bone marrow, extra-nodal or internal organs such as lung and pleura (that can sometimes mimick multiple metastatic lesions), and spleen.…”
Section: Waldenström's Macroglobulinemia (Wm)contrasting
confidence: 81%
See 1 more Smart Citation
“…All patients underwent FDG PET/CT before and after therapy. This imaging procedure was able to detect positive findings in 83 % of the patients, a result in sharp contrast with the data of previous studies carried out with the use of conventional imaging that reported liver, spleen, and lymph node involvement in remarkably lower percentages [79]. At baseline, FDG-avid sites included more frequently lymph nodes, bone marrow, extra-nodal or internal organs such as lung and pleura (that can sometimes mimick multiple metastatic lesions), and spleen.…”
Section: Waldenström's Macroglobulinemia (Wm)contrasting
confidence: 81%
“…Based on large series of patients, including our own cohort of 121 patients [78], it has in fact been shown that the clinical presentation of WM is rather heterogeneous, including lymphadenopathy, hepato-splenomegaly, and polyneuropathy in percentages ranging from 20 to 25 %, signs, and symptoms related to the physical, chemical, and immunologic properties of the IgM monoclonal component, and bone marrow clonal cell expansion of variable extent [79].…”
Section: Waldenström's Macroglobulinemia (Wm)mentioning
confidence: 99%
“…2,5,6 Plasmapheresis rapidly lowers IgM concentrations for immediate disease control. 1 We report for the first time a case of WM with presumed cold-agglutininmediated AIHA refractory to typical therapy, ultimately requiring hematopoietic stem cell transplantation, specifically for anemia control.…”
mentioning
confidence: 98%
“…1 Overproduced IgMs can act as cold agglutinins in WM. Upon exposure to cooler temperatures in the periphery, they cause anemia via binding to the erythrocyte Ii-antigen group and classical complement cascade initiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation